Bone ingrowth observed in a cup removed during revision surgery for early dislocation after primary THA: A case report. (June 2021) - Kitajima, Hironori; Kaneuji, Ayumi; Soma, Daisuke; Fukui, Makoto; Kawahara, Norio
Abstract: Introduction and importance: Recently cementless total hip arthroplasty (THA) has shown good long-term results with excellent stability resulted from the porous coating of the implant. A hydroxyapatite-tricalcium phosphate (HA-TCP) coating on the porous surface is expected to promote bone ingrowth and to improve initial fixation of the implant. Here we report a case of bone ingrowth observed in a cup removed during revision surgery for early dislocation, 37 days after primary THA using a porous coating cup with HA-TCP. Case presentation: A 61-year-old woman who has bilateral osteoarthritis underwent same-day bilateral THA. Both sides used porous coating cups with HA-TCP. Line-to-line technique and screw fixation were utilized. Anterior dislocation of the left hip occurred on days 27 and 31, and we performed cup revision on day 37 after surgery. We noted bone-like tissue on the posterior surface of the cup and in a vacant screw hole. Bone tissue was also confirmed in pathological findings. Clinical discussion: Studies in animals have confirmed early bone ingrowth about 4 weeks after surgery with HA-TCP coated implants. In humans, the earliest report of bone ingrowth in cups is for a cup without HA-TCP coating, detected 5 weeks after surgery. In the present case, we used a porous coating cup with HA-TCP, and bone ingrowth was confirmed at approximately the same time as for the previous case. Conclusion: Early clinical bone ingrowth was confirmed in an HA-TCP coated cup, occurring at about the same time after surgery as in previous reports. Highlights: Cementless THA shows excellent long-term results for porous coating of implant. HA-TCP coating promotes bone ingrowth of mesenchymal cells. Post-THA revision showed good initial fixation with porous coating cup and HA-TCP.